Form and Dialectic in Georg Simmel's Sociology - Schermer, H. author. aut Link
X, 328 p.
Keywords: This book shows that a dialectical conceptual model underpins Georg Simmel's writings. The book provides key examples of social forms – including fashion, the secret and money – as exemplifications of this method. The volume concludes with a reassessment of Simmel's relevance today.